2018
DOI: 10.1038/s41598-018-37157-7
|View full text |Cite|
|
Sign up to set email alerts
|

Propolis-based niosomes as oromuco-adhesive films: A randomized clinical trial of a therapeutic drug delivery platform for the treatment of oral recurrent aphthous ulcers

Abstract: Oromuco-adhesive films for buccal delivery of Propolis extract (PPE) entrapped in niosomes, were prepared to treat oral recurrent aphthous ulcer (RAU). PPE was investigated for antimicrobial compounds. Niosomes composed of span60 and cholesterol were evaluated for particles size, polydispersity index (PDI), zeta-potential, entrapment efficiency and in vitro release. The formed oromuco-adhesive films containing niosomal PPE were evaluated for swelling, mucoadhesion and elasticity. 24 patients suffering from RAU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 63 publications
2
53
0
Order By: Relevance
“…Propolis polyphenols, although beneficially bioactive molecules, pose problems of low bioavailability, and thus may benefit from targeted nanodelivery systems via nanocarriers [56]. In particular, permeation through the buccal mucosa appears to be a promising approach to bypass liver metabolism and release propolis-based nano-formulations and niosomes locally or systemically [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…Propolis polyphenols, although beneficially bioactive molecules, pose problems of low bioavailability, and thus may benefit from targeted nanodelivery systems via nanocarriers [56]. In particular, permeation through the buccal mucosa appears to be a promising approach to bypass liver metabolism and release propolis-based nano-formulations and niosomes locally or systemically [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to increased width of lipid bilayer membrane. Interestingly, Arafa et al ( Arafa et al, 2018 ) stated the increased E.E% of propolis with increased DL which could be attributed to the enhanced capacity of the prepared nanostructure. Unlikely, Results showed that CH% had no effect on E.E % of the prepared PP-Lip.…”
Section: Resultsmentioning
confidence: 99%
“…An interesting approach to enhance the physical stability of niosomes is to obtain a stable dry powder formulation by lyophilization that can later be resuspended in the appropriate solvent before use. In this case, the selection and the concentration of the cryoprotector, along with the parameters of the lyophilization process need to be evaluated to guarantee the stability of the dry powder [107,108]. The analysis of some of the previously described physicochemical parameters on a niosome formulation can be observed in Figure 4.…”
Section: Physicochemical Characterization Of Niosome Nanoparticlesmentioning
confidence: 99%